Upper extremity deep vein thrombosis in hospitalized patients: A descriptive study. Issue 1 (27th November 2013) - Schleyer, Anneliese M.; Jarman, Kenneth M.; Calver, Patty; Cuschieri, Joseph; Robinson, Ellen; Goss, J. Richard
<x xml:space="preserve">Abstract</x> Increasingly, there is a focus on the prevention of hospital‐acquired conditions including venous thromboembolism. Many studies have evaluated pulmonary embolism and lower extremity deep vein thrombosis, but less is known about upper extremity deep vein thrombosis (UEDVT) in hospitalized patients. The objective of this study was to describe UEDVT incidence, associated risks, outcomes, and management in our institution. Using an information technology tool, we reviewed records of all symptomatic adult inpatients diagnosed with UEDVT at an academic tertiary center between September 2011 and November 2012. Fifty inpatients were diagnosed with 76 UEDVTs. Their mean age was 49 years; 70% were men. Sixteen percent had a history of venous thromboembolism; 20% had a history of malignancy. The mean length of stay (LOS) was 24.6 days (range, 2–91 days); 50% were transferred from outside hospitals. Thirty‐eight percent of UEDVTs were in internal jugular veins, 21% in axillary veins, and 25% in brachial veins. Forty‐four percent of patients had UEDVT associated with central venous catheters (CVCs). During hospitalization, 78% were fully anticoagulated; 75% of survivors at discharge. Only 38% were discharged to self‐care; 10% died during hospitalization. Patients with UEDVT were more likely to have CVCs, malignancy, and severe infection. Many patients were transferred critically ill with prolonged LOS and high in‐hospital mortality. Most UEDVTs were treated even in the absence of concurrent lower extremity deep vein thrombosis or pulmonary embolism. Additional research is needed to modify risks and optimize outcomes. Journal of Hospital Medicine 2014;9:48–53. © 2013 Society of Hospital Medicine